The experience of older people in Japan four years after the tsunami. Issue 1 (February 2019) - Kako, Mayumi; Mayner, Lidia
Abstract: Background: When a disaster occurs older people are recognised to be among one of the vulnerable population groups. During the Great East Japan earthquake in 2011, there were numerous unresolved health and social issues for the survivors. Aim of the study: To understand which challenges older people that survived the 2011 disaster faced, which aspects they identified as concerns and what they felt was difficult and possibly could not recover from in the near future. Methods: A qualitative case study method was used. Sixteen participants, living in temporary housing, were interviewed in 2015. The interview data was analysed using thematic analysis. Findings and discussion: Participants (4 men; 12 women) were aged between 65 and 89 years. Seven participants stated that they were healthy although they had minor health issues. Some women had psycho-social health issues brought about by the trauma they experienced, caring for their aging relatives and living in temporary housing. Four themes emerged: feeling grateful to be alive; issues related to health and mental health; the importance of recreational activities and community involvement; feeling of fear, uncertainty and vulnerability. Conclusions: This is the first study to report directly participants' feelings and views after their traumatic experience. All participants were happy to be interviewed and to express their views. Although participants expressed their need for health professional services to be available to support them following traumatic events, these services are yet to be recognised as an essential part of the recovery process.